2010
DOI: 10.21273/horttech.20.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Growing Minds: Evaluating the Relationship between Gardening and Fruit and Vegetable Consumption in Older Adults

Abstract: New dietary guidelines recommend eating more than five servings of fruit and vegetables each day without setting upper limitations. Although older adults tend to report a higher intake of fruit and vegetables than other age groups, over half of the U.S. older population does not meet the recommendation of five daily servings of fruit and vegetables. Research has shown that gardening is one way of improving fruit and vegetable intake. The primary focuses of this study were to examine and compare fruit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 21 publications
2
32
2
Order By: Relevance
“…6,7 Vegetable gardening may provide a holistic approach to improving diet quality, physical activity, body weight status, and psychosocial well-being. [8][9][10][11] Vegetable gardening improves access to fresh produce and has been demonstrated to increase vegetable consumption across several populations. 8,9 Healthy senior adults have been shown to meet physical activity recommendations through gardening.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Vegetable gardening may provide a holistic approach to improving diet quality, physical activity, body weight status, and psychosocial well-being. [8][9][10][11] Vegetable gardening improves access to fresh produce and has been demonstrated to increase vegetable consumption across several populations. 8,9 Healthy senior adults have been shown to meet physical activity recommendations through gardening.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies that address gardening for older adults for fruits and vegetables (Sommerfield et al, 2011), and there are studies that look at the urban environment (Wakefield et al, 2007), these findings are among the first to address older adults harvesting fruits and vegetables in an urban environment. Data from this study support previous studies that found that elderly people found mental health benefits and relaxation in gardening (Wakefield, Yeudall, Taron, et al, 2007); moreover, this study contributes an additional dimension of understanding.…”
Section: Discussionmentioning
confidence: 99%
“…This in return may increase health in a way not otherwise affected. One study that looked at nutritional benefits (Sommerfield, McFarland, Waliczek, & Zajick, 2011) found that gardeners were more likely to consume vegetables than nongardeners. Future research possibilities include the potential for a controlled study looking at nutrition and produce consumption among gardeners and nongardeners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor nutrition is one factor that has been linked to the rising cost of healthcare and the consumption of fruit and vegetables has consistently been linked to improved health (Nestle, 2007;Schlettwein-Gsell, 1992). Research on older adults consistently shows that older populations do not consume the proper numbers of servings of fruit and vegetables on a daily basis (Bowman, 2007;Prochaska et al, 2005;Sommerfeld et al, 2010a;Vitolins et al, 2007). Bisogni et al (2002) reported that older adults who were born during World War II consumed fewer fruit and vegetables due to the rationing of nonbasic caloric needs experienced during this time period.…”
mentioning
confidence: 99%